Inside teacher education challenging prior views of teaching and learning - Bullock, Shawn Michael; SpringerLink (Online service). (Rotterdam SensePublishers, 2011)
Learning to teach is complex. Teacher candidates begin a preservice program with powerful tacit assumptions about how teachers teach based on lengthy apprenticeships of observation over many years as students. Virtually all teacher education programs provide a mixture of coursework and classroom experience. Much has been written about the theory-into-practice approach in teacher education, an approach that assumes teacher candidates who have been provided with instructions about how to teach will be able to recall and apply them in a school setting. In reality, teacher candidates report considerable difficulty enacting theory in practice, to the point that many question the value of coursework. This book takes an in-depth look at five future teachers in one teacher education program, analyzing and interpreting how they and their teacher educators learn from experience during both coursework and practicum experiences. Many assumptions about the complex challenges of teaching teachers are called into question. Is the role of a teacher educator to synthesize research-based best practices for candidates to take to their field placements? Does the preservice practicum experience challenge or reinforce a lifetime of socialized experiences in schools? Must methods courses always be seen by most teacher candidates as little more than sites for collecting resources? Where and how do candidates construct professional knowledge of teaching? The data illustrate clearly that methods courses can be sites for powerful learning that challenges tacit assumptions about how and why we teach.
Electronic reproduction.
Keywords: Teachers -- Training of; Electronic books